An Analysis of Transitivity System Written by English Department Students - Fauzi, Safira; Thohir, Lalu; Zamzam, Ahmad; Melani, Boniesta Zulandha (Journal of English Education Forum (JEEF), 2024)
The research was conducted to identify the process types of transitivity systems used in the narrative texts written by English Department Students and to determine which process type of transitivity systems is used dominantly. This research was descriptive qualitative research on descriptive analysis. The research participants were students of the English Department. This research uses three research instruments, namely the researcher himself, narrative document files, and distribution sheet of process types. In collecting the data, the researcher used the documentation method and purposive sample technique to select the data. The data analysis was done with transitivity system analysis, adapted from the lecture of the Functional Grammar course, and then several steps based on thematic coding by Braune & Clark, were applied. The triangulation technique was used to get the dependability of the data through re-checking and expert judgment. The research found that the six process types in each text of the six narratives that were the data sample were not evenly used. Three process types, behavioral, verbal, and existential, are only used in several narrative texts written by English Department Students. Moreover, the six process types of transitivity system are realized in narrative texts written by English Department Students overall. The most dominant process is the material process, which occurs 155 times out of the 346 processes that emerged, followed by behavioral processes (8 or 2.31%), mental processes (100 or 28.90%), verbal processes (5 or 1.44%), relational processes (76 or 21.96%), and existential processes (2 or 0.58%).